Response of maize (Zea mays) to the application of foliar fertilizers in the Sudan and Guinea savanna zone of Nigeria - Jemo, M.; Nwoke, C.; Pypers, Pieter; Vanlauwe, Bernard (Wiley, 2015)
Soil fertility problems resulting in low maize yields in smallholder farms are common in the West African moist savanna. The effectiveness of commercial foliar fertilizers in improving maize growth and yield was evaluated in three savanna agro-ecological zones of Nigeria in two steps. In step one, eight commercial foliar fertilizers were assessed in a greenhouse study with two soil types using maize ( Zea mays L. cv. 2004 TZE-Y POPDT STR C4). The treatments included a control and a reference that received the optimum concentrations of nutrients. In step 2, three promising products from the greenhouse study ( Turbotop, Agroleaf General , and Agroleaf high- P ) were evaluated under field conditions to validate the efficacy of products to enhance crop growth and yield. The foliar products were applied at the rate of 5 kg ha –1 . The treatments also in- cluded three rates of P application (0, 30, and 60 kg P ha –1 ) as triple super phosphate (TSP) with or without foliar fertilizers. In the greenhouse study, differences in maize shoot dry matter yield and N and P concentrations, attributable to the spraying of the commercial foliar fertilizers, were observed for both soils. Spraying Turbotop, Agroleaf General , and Agroleaf high-P gave the highest shoot dry biomass and N and P uptake compared to other products. Under field condi- tions, foliar spraying of Agroleaf high-P significantly increased the shoot dry biomass of maize compared with the 0P treatment in all locations. The grain yield of maize ranged from 1 to 4 t ha –1 with significant differences across sites. Products with high concentrations of P and N in their formulation improved maize yield suggesting that appropriate management of P and N re- sources is a prerequisite for a sustainable maize intensification in the savanna agro-ecologies.Soil fertility problems resulting in low maize yields in smallholder farms are common in the West African moist savanna. The effectiveness of commercial foliar fertilizers in improving maize growth and yield was evaluated in three savanna agro-ecological zones of Nigeria in two steps. In step one, eight commercial foliar fertilizers were assessed in a greenhouse study with two soil types using maize ( Zea mays L. cv. 2004 TZE-Y POPDT STR C4). The treatments included a control and a reference that received the optimum concentrations of nutrients. In step 2, three promising products from the greenhouse study ( Turbotop, Agroleaf General , and Agroleaf high- P ) were evaluated under field conditions to validate the efficacy of products to enhance crop growth and yield. The foliar products were applied at the rate of 5 kg ha –1 . The treatments also in- cluded three rates of P application (0, 30, and 60 kg P ha –1 ) as triple super phosphate (TSP) with or without foliar fertilizers. In the greenhouse study, differences in maize shoot dry matter yield and N and P concentrations, attributable to the spraying of the commercial foliar fertilizers, were observed for both soils. Spraying Turbotop, Agroleaf General , and Agroleaf high-P gave the highest shoot dry biomass and N and P uptake compared to other products. Under field condi- tions, foliar spraying of Agroleaf high-P significantly increased the shoot dry biomass of maize compared with the 0P treatment in all locations. The grain yield of maize ranged from 1 to 4 t ha –1 with significant differences across sites. Products with high concentrations of P and N in their formulation improved maize yield suggesting that appropriate management of P and N re- sources is a prerequisite for a sustainable maize intensification in the savanna agro-ecologies.Soil fertility problems resulting in low maize yields in smallholder farms are common in the West African moist savanna. The effectiveness of commercial foliar fertilizers in improving maize growth and yield was evaluated in three savanna agro-ecological zones of Nigeria in two steps. In step one, eight commercial foliar fertilizers were assessed in a greenhouse study with two soil types using maize ( Zea mays L. cv. 2004 TZE-Y POPDT STR C4). The treatments included a control and a reference that received the optimum concentrations of nutrients. In step 2, three promising products from the greenhouse study ( Turbotop, Agroleaf General , and Agroleaf high- P ) were evaluated under field conditions to validate the efficacy of products to enhance crop growth and yield. The foliar products were applied at the rate of 5 kg ha –1 . The treatments also in- cluded three rates of P application (0, 30, and 60 kg P ha –1 ) as triple super phosphate (TSP) with or without foliar fertilizers. In the greenhouse study, differences in maize shoot dry matter yield and N and P concentrations, attributable to the spraying of the commercial foliar fertilizers, were observed for both soils. Spraying Turbotop, Agroleaf General , and Agroleaf high-P gave the highest shoot dry biomass and N and P uptake compared to other products. Under field condi- tions, foliar spraying of Agroleaf high-P significantly increased the shoot dry biomass of maize compared with the 0P treatment in all locations. The grain yield of maize ranged from 1 to 4 t ha –1 with significant differences across sites. Products with high concentrations of P and N in their formulation improved maize yield suggesting that appropriate management of P and N re- sources is a prerequisite for a sustainable maize intensification in the savanna agro-ecologies.Soil fertility problems resulting in low maize yields in smallholder farms are common in the West African moist savanna. The effectiveness of commercial foliar fertilizers in improving maize growth and yield was evaluated in three savanna agro-ecological zones of Nigeria in two steps. In step one, eight commercial foliar fertilizers were assessed in a greenhouse study with two soil types using maize ( Zea mays L. cv. 2004 TZE-Y POPDT STR C4). The treatments included a control and a reference that received the optimum concentrations of nutrients. In step 2, three promising products from the greenhouse study ( Turbotop, Agroleaf General , and Agroleaf high- P ) were evaluated under field conditions to validate the efficacy of products to enhance crop growth and yield. The foliar products were applied at the rate of 5 kg ha –1 . The treatments also in- cluded three rates of P application (0, 30, and 60 kg P ha –1 ) as triple super phosphate (TSP) with or without foliar fertilizers. In the greenhouse study, differences in maize shoot dry matter yield and N and P concentrations, attributable to the spraying of the commercial foliar fertilizers, were observed for both soils. Spraying Turbotop, Agroleaf General , and Agroleaf high-P gave the highest shoot dry biomass and N and P uptake compared to other products. Under field condi- tions, foliar spraying of Agroleaf high-P significantly increased the shoot dry biomass of maize compared with the 0P treatment in all locations. The grain yield of maize ranged from 1 to 4 t ha –1 with significant differences across sites. Products with high concentrations of P and N in their formulation improved maize yield suggesting that appropriate management of P and N re- sources is a prerequisite for a sustainable maize intensification in the savanna agro-ecologies.